Enhanced alcohol metabolism and sleep quality with continuous positive airway pressure following alcohol consumption - Hyun Jun Kim; Do-Yang Park; Wee Gyo Lee; Kang Il Lee; Jin Ji Jung; Han Sang Lee; Sang In Hwang; Ji Hyun Park; Bumhee Park (Scientific Reports)
Abstract We aimed to examine the effect of continuous positive airway pressure on sleep quality and alcohol metabolism after alcohol consumption. Men (n = 53) aged ≥ 19 years with sleep disorders who regularly consumed an average of ≥ 1.0 g of alcohol/kg of bodyweight, were free of serious diseases (including liver disorders), and underwent polysomnography and continuous positive airway pressure titration between January 2016 and July 2021 were included. Participants drank a high dose of a traditional Korean liquor at a rate of 1.0 g/kg of bodyweight for 1 h. The main outcome measures included polysomnography results and blood and breath ethanol and acetaldehyde concentrations after alcohol consumption before and after sleep. Statistical analyses were performed using R software, version 4.0.5 (R Foundation, Vienna, Austria). Continuous positive airway pressure enhanced sleep quality after alcohol consumption, with oxygen significantly improving the metabolism of acetaldehyde over that of ethanol. Breath and blood sample analyses and polysomnography results revealed that continuous positive airway pressure improved sleep quality by reducing apnea–hypopnea index by 27.32 ± 24.87 (p < 0.001), increasing rapid eye movement sleep by 2.08 ± 6.74% (p < 0.05), and enhancing acetaldehyde breakdown by 21.2% (p < 0.001), while its effect on ethanol breakdown (4–5%) was not statistically significant. Continuous positive airway pressure is recommended after alcohol consumption for individuals with sleep apnea to enhance sleep quality.